INFLUENZA VIRUSES CIRCULATING IN MARINE MAMMALS POPULATIONS OF THE HOLARCTIC - Kydyrmanov , A. (Eurasian Journal of Applied Biotechnology, 2014)
This review paper presents information on epizootic among marine mammals caused by influenza viruses of A and B types. The role of these animals in the ecology and evolution of the pathogen is being discussed. There are described the cases of involving of marine mammals to circulation of the pandemic “swine” influenza A (H1N1) virus. The possibility of seal infection with a wide range of influenza viruses through direct transmission without prior adaptation is suggested. It is noted that the character and intensity of binding of influenza A viruses of different origin with epithelial cells of the respiratory organs of marine mammals is a determining factor in their susceptibility to the infection, as well as its productivity features and pathogenesis. There is emphasized a statement that marine pinnipeds can serve as one of the reservoirs of human influenza B virus in the nature. Virological and serological data about influenza A virus (H7N7) circulation among Caspian seals are provided. The absence in the literature any data on phylogenetic and pathobiological properties of this epizootic virus is specified. The necessity for integrated environmental and virological monitoring of influenza viruses circulating in the population of seals in the Kazakh sector of the Caspian Sea is concluded.